Model‐Based Selection and Recommendation for Subcutaneous Abatacept Dose in Patients With Polyarticular Juvenile Idiopathic Arthritis. (18th January 2021) - Gandhi, Yash; Passarell, Julie A.; Roy, Amit; Murthy, Bindu
Abstract: The selective T‐cell costimulation modulator abatacept is approved for treatment of adult rheumatoid arthritis (RA) and polyarticular juvenile idiopathic arthritis (pJIA; 6‐17 years [intravenous] and 2‐17 years [subcutaneous]). An extrapolation approach was taken to determine subcutaneous weight‐tiered doses of abatacept to evaluate in patients with pJIA. Population pharmacokinetic (PPK) and exposure‐response (E‐R) analyses were conducted to determine whether the weight‐tiered subcutaneous regimen provides near‐maximal efficacy and is therapeutically comparable to the intravenous regimen in patients with pJIA aged 2‐17 years. Combined study data from intravenous or subcutaneous abatacept were used to assess clinically relevant exposure outcomes. The PPK model was developed with data from 13 phase 2/3 studies in RA and pJIA; the E‐R model for the American College of Rheumatology pediatric scores (JIA‐ACR 30/50/70/100 responses) in month 4 was developed with data from 2 phase 3 pJIA studies. Predefined covariates were investigated in both analyses. PPK model‐predicted exposures were steady‐state peak, trough (Cminss ), and time‐averaged concentrations. Abatacept PK was characterized by a linear 2‐compartment model (zero‐order intravenous infusion, first‐order subcutaneous absorption, first‐order elimination); body weight was the only clinically relevant covariate. Cminss was the best exposure predictor for the JIA‐ACR response: log odds for response increased in proportion to log‐transformed Cminss ; JIA‐ACR30 approached a plateau when Cminss ≥ 10 μg/mL. The PPK and E‐R analyses demonstrated that the weight‐tiered subcutaneous and intravenous abatacept dosing regimens provide near‐maximal efficacy and are clinically comparable across children with pJIA who are > 2 years old.